Histopathological studies of the heart in three lines of broiler chickens. Issue 2 (3rd March 2016) - Gesek, M.; Otrocka-DomagaŁa, I.; SokóŁ, R.; PaŹdzior-Czapula, K.; Lambert, B. D.; WiŚniewska, A. M.; Żechowicz, M.; Mikiewicz, M.; Korzeniowska, P.
Abstract: The aim of this study was to analyse the morphological lesion pattern of the heart of broiler chickens (Cobb 500, Hubbard F15 and Ross 308) during fattening with no clinical signs of disease and to determine the most susceptible period for the occurrence of morphological lesions. The most frequently diagnosed lesions in each genetic line were degeneration of the fibres with vacuolation, congestion of cardiac muscle, oedema and vacuolisation of the Purkinje cells. The highest numbers of morphological lesions were observed on d 38, 31 and 10 of life. The lesions were most numerous in the septum, followed by the left and right ventricles. Ischaemic cardiomyocytes were also most numerous on d 38 of life and in the left ventricle. Overload of cardiac muscle, prolonged hypoxia and increasing body weight on d 38 are the likely reasons for the largest number of lesions and ischaemic fibres, which may lead to heart failure.